Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Talking Stick Terhadap Hasil Belajar IPA Siswa Kelas V SD Inpres Bakung I Kota Makassar - Nurhayati Selvi; Nur Afni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstrak: The Effect of Applying the Talking Stick Type Cooperative Learning Model on Science Learning Outcomes of Grade V Students of SD Inpres Bakung I Makassar City. This study aims to determine the application of the talking stick type cooperative learning model, the difference in learning outcomes in science subjects, and the Talking Stick learning model to student learning outcomes in science subjects class V SD Inpres Bakung I Makassar City. The approach used in this study is quantitative with an ex post facto type of research with a questionnaire stage. The population and sample of this study were grade V students of SD Inpres Bakung I Makassar City with a total of 19 students, sampling using saturated sampling techniques. The results showed that (1) The Talking Stick type cooperative learning model in science learning was carried out by distributing questionnaires. (2) The results of students' science learning after the implementation of the Talking Stick type cooperative learning model showed an improvement. (3) TheTalking Stick type cooperative learning model affects the science learning outcomes of grade V students of SD Inpres Bakung I Makassar City. This can be seen from the results of the t test analysis which proves that the calculated t value = 3.069 > ttable = 2.093 with a p-value of < 0.05.